Cathode Performance of Co-Doped Li2O with Specific Capacity (400 mAh/g) Enhanced by Vinylene Carbonate. Issue 4 (16th February 2017) - Kobayashi, Hiroaki; Hibino, Mitsuhiro; Kubota, Yuki; Ogasawara, Yoshiyuki; Yamaguchi, Kazuya; Kudo, Tetsuichi; Okuoka, Shin-ichi; Ono, Hironobu; Yonehara, Koji; Sumida, Yasutaka; Mizuno, Noritaka
Abstract : A Co-doped Li2 O (CDL) was synthesized using a planetary ball mill and examined as a cathode material for lithium-ion batteries. When vinylene carbonate, which is often employed as an additive in an electrolyte, was used not only as an additive in the electrolyte but also as a treatment agent for CDL, the specific capacity of CDL was greatly enhanced and the charge–discharge cycles with specific charging and discharging capacities of 400 mAh/g could be repeated for more than 50 times. Co K -edge XANES spectroscopy and quantitative analysis of peroxide species revealed that the redox reactions of cobalt ions, formation/neutralization of O 2 p electron holes, and generation/annihilation of peroxide species occurred during the charge–discharge process.